Implementation of Codeigniter 3 Framework in Creating Web-Based Sales System and Company Profile of A Swallow Consultant - Yusuf Wahyu Setiya Putra; Fatimah Nur Arifah; Sri Waluyo (Institut Teknologi Bisnis AAS Indonesia, 2022)
The developments in telecommunications and technology rank first in order to bring about changes in the social conditions of the world. Business opportunities by utilizing the internet are also increasing, especially for promoting goods and services. CV Andromeda Multi Sarana or commonly known as AMS is a company engaged in Swallow consultancy. The company is engaged in trade and services. In supporting its trading activities, AMS requires a website. Currently, AMS only has one company profile website, while the processing and sales are still carried out using manual recording through Microsoft Excel application. This can also cause ineffectiveness and inefficiency of reports given by administrative staff to their superior. In this study, the researchers provide a solution to the problem by creating online store sales system and company profile using a website-based Codeigniter 3 framework. This study aims to provide solutions to existing problems and facilitate users in making transactions with company admins.